2008
DOI: 10.1007/s10802-007-9203-7
|View full text |Cite
|
Sign up to set email alerts
|

The Shifting Subtypes of ADHD: Classification Depends on How Symptom Reports are Combined

Abstract: Research on the correlates of ADHD subtypes has yielded inconsistent findings, perhaps because the procedures used to define subtypes vary across studies. We examined this possibility by investigating whether the ADHD subtype distribution in a community sample was sensitive to different methods for combining informant data. We conducted a study to screen all children in grades 1-5 (N = 7847) in a North Carolina County for ADHD. Teachers completed a DSM-IV behavior rating scale and parents completed a structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 61 publications
6
21
1
3
Order By: Relevance
“…This pilot study also compared the differences between subtypes of ADHD, although some authors have come to question the validity of the subtypes 12 . Studies comparing the impairment between the subtypes of ADHD in adults, are rare 13 , usually comparing the combined and inattentive subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…This pilot study also compared the differences between subtypes of ADHD, although some authors have come to question the validity of the subtypes 12 . Studies comparing the impairment between the subtypes of ADHD in adults, are rare 13 , usually comparing the combined and inattentive subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…One measurement issue related to eligibility criteria involves the choice of informants and decision rules used to determine a diagnosis of ADHD. Both have been shown to influence the diagnostic decisions (Rowland et al, 2008;Valo & Tannock, 2010) and we examined the variability across studies in this area. Another measurement issue involves the choice of outcome measures.…”
Section: Characteristics Affecting Outcomesmentioning
confidence: 99%
“…Many of the studies did not indicate the basis for deciding when symptoms were considered present. Two studies in the past five years have revealed that these subtle decisions can lead to important differences in terms of which children are diagnosed with ADHD and which are not (Rowland et al, 2008;Valo & Tannock, 2010). The results of treatment outcome studies may also be affected by these variations in how diagnoses are determined.…”
Section: Characteristics Of Measurementmentioning
confidence: 99%
“…In some studies, parents reported more severe ADHD behaviors than did teachers (e.g., Sullivan and Riccio 2007), whereas in others, teachers reported more severe symptoms (e.g., Amador-Campus et al 2006). Interestingly, there is sometimes greater agreement between parents and teachers regarding specific symptoms of ADHD than there is for ADHD subtype (Mitsis et al 2000;Rowland et al 2008). Mitsis et al (2000) also noted greater parent-teacher agreement for hyperactive/impulsive symptoms than for inattentive symptoms.…”
Section: Informant Concordance and Medication Treatmentmentioning
confidence: 99%
“…A key issue in this assessment is the congruence between informants providing information about the child's functioning. Although positive correlations between parent and professional ratings have been noted with regard to developmental status (Dinnebeil and Rule 1994), other studies have revealed informant discrepancies in reports of behavioral and emotional functioning (Achenbach et al 1987;Mitsis et al 2000;De Los Reyes and Kazdin 2005;Rowland et al 2008).…”
Section: Adhd Behavioral Ratings In Children With and Without Asdsmentioning
confidence: 99%